Diverse Marinimicrobia bacteria may mediate coupled biogeochemical cycles along eco-thermodynamic gradients - Alyse K. Hawley (Nature Portfolio, 2017)
Little is known about Marinimicrobia, a group of bacteria that are prevalent in the oceans. Here, the authors study global populations of Marinimicrobia using single-cell genomics, metagenomics and metatranscriptomics, showing potential co-metabolic interactions and participation in the sulfur and nitrogen cycles.